2022
DOI: 10.51817/jpdr.v2i2.218
|View full text |Cite
|
Sign up to set email alerts
|

Teacher Strategies in Directive Speech Act on the Growth of Pancasila Character in Students

Abstract: This study aims to find the form and function of teacher speech strategies in the learning process in the classroom in Indonesian. This research uses a qualitative descriptive approach with a pragmatic approach. The research data were obtained through observation and in-depth interviews. Data analysis is carried out by using qualitative techniques by reducing data, presenting data, and drawing conclusions from existing data. The results showed that the use of directive speech acts was of the type of ordering, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…In addition, they also believe that from a parent's perspective, with indirect speech, parents will not feel hurt when their child refuses. However, direct and indirect affirmation speech acts can express the speaker's feelings and convey the affirmation's meaning (Alfaleh, 2019;Ibraheem, 2018;Maruti, 2022;Sari et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, they also believe that from a parent's perspective, with indirect speech, parents will not feel hurt when their child refuses. However, direct and indirect affirmation speech acts can express the speaker's feelings and convey the affirmation's meaning (Alfaleh, 2019;Ibraheem, 2018;Maruti, 2022;Sari et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…She argued that the dominant finding was assertive/ representative to state and explain certain things. Sari et al (2022) analyzed the directive speech act used by the teacher in forming the character of Pancasila to students using an indepth interview method, and the result showed that ordering is the most common type since it makes the expression more apparent without further do. Santoso & Sugiharto (2022) identified the use of directive speech acts by ten teachers during distance learning in Batang District Central Java elementary school students.…”
Section: Introductionmentioning
confidence: 99%
“…At the time of the ancient Greeks, rhetoric was part of the responsibility for democracy, but in Rome rhetoric was the ability to survive in political situations (Griffin, 2019). The rhetoric that forms the basis of a speech can affect the audience so that it can change or influence someone's personality (Sari et al, 2022).…”
Section: Introductionmentioning
confidence: 99%